PENGARUH PENERAPAN TEKNIK ICE BREAKING TERHADAP PEMBELAJARAN PESERTA DIDIK KELAS XII SEKOLAH MENENGAH ATAS DI KABUPATEN TAKALAR - syafriwana, syafriwana (Dahzain Nur, 2024)
The aim of this research is to explore the idea of moderation in various dimensions of human life. The method used is a literature review, which involves searching for and analyzing information sources in both print and digital forms related to moderation. The researcher conducted searches in libraries and utilized various web search engines to collect relevant data. The literature study activities involved reading, note-taking, and processing information from various sources such as books, journals, documents, and publications in both print and electronic forms. The findings of this research indicate that moderation in a religious context is consistency in following the teachings of Allah. This fosters a moderate attitude among Muslims, which is balanced in practicing religion and social interactions in the world. The Qur'an and the understanding of scholars affirm the condition of Muslims as a community that upholds goodness, justice, and balance, without adopting an extreme stance in religion, yet not neglecting their religious obligations. Moderation enables people to act justly and become role models for others. The concept of moderation applies not only to a single aspect of life but encompasses all aspects, with balanced and mature regulation.